Risk management in open prisons: A critical analysis and research agenda - Goodley, Gary (Probation journal, 2023)
Open prisons offer a unique contribution to the community resettlement of those serving custodial sentences. However, the evidence base for the efficacy of open prisons is limited and their existence is frequently scrutinised following adverse events including prisoner absconding and re-offending. This paper critically evaluates open prisons’ efficacy and the effective management of risk in this environment. We present a research agenda which aims to delineate the potential mechanisms of open prisons that rehabilitate offenders, while maintaining the safety of these environments. We emphasise the importance of an improved understanding of risk manifestation, and the need to evaluate existing risk management protocols.